AGENDA SETTING MEDIA DALAM PEMBERITAAN PERANG ISRAEL-PALESTINA DI CNN.COM DAN AL JAZEERA.COM - Herlina, Oktafiani (Jurnal Ilmu Komunikasi AKRAB, 2024)
Agenda Setting Theory is a theory used in mass communication to influence the public. Media build issues which are more important than other issues because of its ability to influence and develop public opinion. CNN and Al Jazeera are two major mass media that represent the West and the East. They have a setting agenda that can not be separated from media agenda setting, the public agenda setting, and the media policy agenda. The purpose of this research is to get answer how agenda setting influence the two media and how it influences reporting on the Israeli-Palestinian war. The method used is to describe texts using framing analysis with agenda setting theory. As the results, CNN and Al Jazeera are influenced by the vision and mission of these media as well as Western and Middle Eastern ideologies. The Public agenda setting and public policy agenda in the media is influenced by social and political system and the prevailing values in which the media is raised.